2011
DOI: 10.1074/jbc.m111.261925
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol- and Sphingolipid-rich Microdomains Are Essential for Microtubule-based Membrane Protrusions Induced by Clostridium difficile Transferase (CDT)

Abstract: Clostridium difficile toxin (CDT) is a binary actin-ADP-ribosylating toxin that causes depolymerization of the actin cytoskeleton and formation of microtubule-based membrane protrusions, which are suggested to be involved in enhanced bacterial adhesion and colonization of hypervirulent C. difficile strains. Here, we studied the involvement of membrane lipid components of human colon adenocarcinoma (Caco-2) cells in formation of membrane protrusions. Depletion of cholesterol by methyl-␤-cyclodextrin inhibited p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 59 publications
0
47
0
Order By: Relevance
“…The methodology was adapted from protocols that were previously established for the recombinant production of various other clostridial toxins (11,17,20,22). The B. megaterium expression system often offers an advantage over conventional bacterial expression systems (e.g., Escherichia coli) in producing clostridial toxins, obviously due to a similar codon usage of the related genera Bacillus and Clostridium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology was adapted from protocols that were previously established for the recombinant production of various other clostridial toxins (11,17,20,22). The B. megaterium expression system often offers an advantage over conventional bacterial expression systems (e.g., Escherichia coli) in producing clostridial toxins, obviously due to a similar codon usage of the related genera Bacillus and Clostridium.…”
Section: Discussionmentioning
confidence: 99%
“…The components of C. botulinum C2 toxin (C2I and C2II) and C. difficile transferase (CDTa and CDTb) were purified from Escherichia coli and Bacillus megaterium, respectively, as described elsewhere, and binding components (C2II and CDTb) were activated by protease treatment (3,5,20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the plasma membrane would favor more planar-like conformations, explaining the smoothing of the cell surface and the retraction of disconnected ICNs (Figure 2 and Figure 5A). Since it has been recently shown that cholesterol-sphingomyelin nanodomains were essential for microtubule-based protrusion growth, 44 it could be also possible that the stability of the ICN depends on the binding of microtubules to the ICN membrane through cholesterol-based membrane nanodomains.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data have suggested that CDT results in the formation of microtubule-based protrusions on epithelial cells that might increase the adherence and colonization of C. difficile 142 .…”
Section: Binary Toxin Cdtmentioning
confidence: 99%